Помогите еееееееееееееееееееееееееее

0 голосов
37 просмотров

Помогите еееееееееееееееееееееееееее


image

Алгебра | 37 просмотров
Дано ответов: 2
0 голосов

√(5-х²)+х=3
√(5-х²)=3-х
5-х²>0;х²<5;|х|<√5<br>3-х>0;х<3;ОДЗ |х|<√5<br>(√5-х²)²=(3-х)²
5-х²=9-6х+х²
2х²-6х+4=0
х²-3х+2=0
Д=9-8=1
х=(3±1)/2
х1=2;х2=1
ответ 2;1

(30.0k баллов)
0 голосов

Решение:
√(5-х²) + х = 3
√(5-х²) = 3 - х
5 -х² = (3 - х)²
5 - х² = 9 + х² - 6х
2х² - 6х + 4 = 0
х² - 3х + 2 = 0
D = b² - 4ac = 9-8=1;
x1 = (3+1):2= 2
x2= (3-1):2=1
Проверка:
Если х = 2, то √(5-2²) + 2 = 3, 1+2=3-верно.
Если х = 1, то √(5-1²) + 1 = 3, 2 + 1=3-верно.
Ответ: 1; 2.

(29.9k баллов)